EVALUATION OF THE LOGISTICS PERFORMANCE - Carvalho de Oliveira, Rômulo (2014)
This article aims at producing a contribution on the logistics, specifically the evaluation of the logistics performance, through the construction of new performance indicators. At the present moment, in Europe and in the United States, the logistics performance is one of the key factors for the business competition, turning into a solution for a sustainable logistic management, exploring two tendencies that has approximated the services suppliers to their clients: the more enlarged collaboration and the replacement of the physical movements for better circulation of the flow of information. In that sense, the companies that belong to the group of those companies that worry with their competitive position should be evaluated in relation to their logistics performance or the relative success about the progress of the innovation of their logistic system, as well as their more or less sustainable behaviour.